Wavelet transform-based fault detection method for hydrogen energy-based distributed generators - Bayrak, Gökay (Pergamon-Elsevier Science Ltd, 2018)
Integration of hydrogen energy-based distributed generators (HEBDGs) to the main grid causes some power quality (PQ) problems. The conventional fault detection methods fail to detect some PQ disturbances, thus intelligent methods are proposed in the literature recently. This paper focuses on developing a wavelet transform (WT)-based fault detection method for HEBDG systems to detect PQ disturbances in the low-voltage grid connection. The proposed method uses the discrete WT and Daubechies wavelets of order 4 to detect the voltage swell, voltage sag, voltage interruption and transient disturbances in a HEBDG system. The performance of the WT-based method is also compared with the conventional fault detection methods, and using the time-frequency domain analysis by WT increases the stability of the proposed method. The results verify that the conventional methods are not capable of detecting some PQ disturbances properly, but the proposed WT-based method is more reliable according to the conventional methods. (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
International Advanced Researches and Engineering Congress (IAREC) -- NOV 16-18, 2017 -- Osmaniye, TURKEY
Keywords: Wavelet transform; Hydrogen energy; Distributed generation; PQ disturbances